A study on growth and pyrolysis characteristics of microalgae using Thermogravimetric Analysis-Infrared Spectroscopy and synchrotron Fourier Transform Infrared Spectroscopy. (April 2017) - Li, Fanghua; Srivatsa, Srikanth Chakravartula; Batchelor, Warren; Bhattacharya, Sankar
Highlights: High CO2 (10%) concentration increased algae growth rate and total lipid content. Effects of temperature and heating rate in pyrolysis characteristics investigated. Nitrogen functional groups began to decompose at a temperature range of 250–300 °C. Lipid functional groups completely disappeared at a temperature range of 400–500 °C. Oxygen and nitrogen functional groups still remained at 550 °C. Abstract: This two-part study firstly investigated Tetraselmis suecica grown in different CO2 (0.04–15% v/v) concentration through indoor and outdoor cultivation systems. A high CO2 concentration led to a high lipid content, and low nitrogen and oxygen content, which are desirable for transport fuel production. Pyrolysis characteristics were investigated by TG-IR and synchrotron IR microscopy. The results show Tetraselmis suecica grown in 10% CO2 had the highest decomposition rate corresponding to more volatile products produced during the main thermal cracking stage and derived from protein-and lipid-corresponding functional groups. Moreover, a high reaction temperature and CO2 concentration resulted in a low retention of surface functional groups. The nitrogen functional groups initially decomposed at a temperature range of 250–300 °C and still remained at 550 °C, while the lipid-corresponding functional groups completely disappeared at a temperature range of 400–500 °C. Besides, the decomposition of chemical components followed the order of carbohydrate, protein and lipid.